Entrepreneurship Growth in Mizoram with reference to the Entrepreneurship Development Scheme (EDS) - KC Malsawmtluangi Prof. Laldinliana (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This paper studies entrepreneurship growth and improved entrepreneurial spirit in Mizoram over the past years with reference to the Entrepreneurship Development Scheme (EDS) under the New Economic Development Policy (NEDP). It reports the framework, activities, programmes and achievements of the EDS, along with the rising entrepreneurial ecosystem among the youth of Mizoram in particular.